Savoir environnemental local et scientifique : entre la révolution, la gouvernance nationale et le développement durable à Cuba - Sabrina Doyon (VertigO, 2005)
This article shows how in Cuba people have for a while considerably minimized the importance of their local environmental knowledge and afterwards reemphasized it. Indeed, after the Revolution, the state sought to promote proletarian values and encouraged the people to put an end to their subsistence activities. However, with the advent of the economic crisis of the 1990s, the population had to rediscover and re-invent a local knowledge in order to exploit its natural resources and survive. In the Las Canas community, this process took place in parallel with a sustainable development project promoted by a regional university. But the scientific discourses of the promoters did not succeed in convincing the local population to modify its relations to environment. This article underlines how scientific knowledge was rather re-appropriated and re-interpreted by the later and discusses the consequences of this situation upon the local economy.